The Impact of Economic Globalization on CO2 Emissions: The Case of NAFTA Countries - Kalayci, Cemalettin; Hayaloglu, Pınar (International Journal of Energy Economics and Policy, 2018)
International trade with the economic globalization gaining wide currency has brought along the environmental problems. Transition to environment-friendly high-tech products and schemes in developed countries alleviated the impacts of these problems whereas underdeveloped environmental standards in developing countries still cause deterioration in the environmental quality. For this reason, there are different views on the environmental impacts of globalization. The study investigates the impact of globalization and trade openness on CO2 emissions with reference to the NAFTA countries. Employing panel-data analysis, the study relies on the annual data for a period of 1990-2015. The findings reveal that there is a positive relationship between economic globalization and trade openness, and CO2 emissions. The study further tests the validity of Environmental Kuznets Curve for the target countries. To this end, the research identifies a positive-direction relationship in both linear and square forms between CO2 emissions and economic growth. Keywords: Economic Globalization, CO2 Emissions, Environmental Kuznets Curve JEL Classifications: C33, F18, F64, Q50 DOI: https://doi.org/10.32479/ijeep.7233